The repercussions of Covid-19 on communication and consumer behavior: A longitudinal study of generation Z (Revista de Investigaciones Universidad del Quindío, 2023)
Today communication plays an important role for organizations. To such a magnitude, that it was a crucial part for companies when Sars-Cov-2 (Covid-19) appeared, and the restriction of physical contact due to the social isolation imposed by the WHO worldwide. For this reason, the main purpose of this study was to analyze what were the changes in communication before, at the beginning and during the pandemic, especially in young Z. Methodology was empirical-analytical descriptive, based on the quantitative method through the application of a structured questionnaire with different questions, in three stages at different times before Covid-19 (2019), during (2020) and post-Covid-19 stage (2021). Main findings, the total number of participants were 1,079 young people, all belonging to the Z generational cohort, who stated that they had at least 2 devices with internet access, surfing around 3 to 4 hours a day. Undoubtedly, they have a great preference for digital communication (social networks), WhatsApp being the social network with the greatest pleasure, and they consider communication through social networks important for their daily lives. Limitations, the results obtained from the study cannot be considered determinants of the behavior of the young Z, because the study only contemplates the young Z of Culiacán, however, there may be some coincidences with other states, nations and continents.
Keywords: Communication; Z Young; global generation; Covid-19